1983
DOI: 10.1177/000348948309200611
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Middle Ear Ventilation: The Right Tube in the Right Place

Abstract: Premature extrusion of ventilating tubes continues to plague both doctor and patient. Migrating epithelium on the lateral surface of the drum has been identified as the principal cause of tube migration and extrusion. This information dictates insertion of a tube in an area where the migrating forces tend to keep the tube in place instead of encouraging rejection. When optimally placed, tubes specifically designed for long-term ventilation will function four times longer than randomly placed conventional tubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…After removal of cerumen and disinfection with 0.5 per cent iodine solution, an incision is made in the tympanic membrane. Despite previous studies describing the advantages of an anterosuperior incision, 8 we prefer an incision in the posteroinferior quadrant. Fluid is aspirated from the middle ear.…”
Section: Methodsmentioning
confidence: 94%
“…After removal of cerumen and disinfection with 0.5 per cent iodine solution, an incision is made in the tympanic membrane. Despite previous studies describing the advantages of an anterosuperior incision, 8 we prefer an incision in the posteroinferior quadrant. Fluid is aspirated from the middle ear.…”
Section: Methodsmentioning
confidence: 94%
“…By 1959, he had adapted this further, producing the first flanged tube moulded of polypropylene. 39 In 1965, he designed a Teflon tube with a sloping flange which was easier to insert through a smaller incision. Although content with its success, he patented the ''Armstrong V'' in 1981.…”
Section: The Second Eramentioning
confidence: 99%
“…He believes that an incision at any other site will lead to premature extrusion of the tube, whereas ''the right tube in the right place'' will remain in situ for ''two years, and sometimes for six or more''; the ''right tube'' was one of his own designs. 39 Myringotomy became a standard treatment for glue ear, with or without adenoidectomy, and a survey of UK ENT surgeons in 1977 indicated that 50% inserted a grommet following myringotomy. 40 Ninety-one percent of American otolaryngologists found ventilating tubes to be more effective than antibiotics in preventing acute otitis media, and 99.4% of those surveyed were using grommets regularly.…”
Section: The Second Eramentioning
confidence: 99%
“…20 What is rarely discussed is the fact that the epithelium constitutes just one of several layers of the tympanic membrane. The postulate has been that a tube placed in the anterosuperior quadrant will stay longer due to the pattern of epithelial migration.…”
Section: Quadrant Of Tube Insertionmentioning
confidence: 99%